Pengaruh Aspek MICE Terhadap Kunjungan Wisatawan Ke Kota Malang Di Era New Normal - Aisya Lowine Sativa; Irwan Yulianto (Journal of Event, Travel and Tour Management, 2021)
This research was conducted to determine the influence of MICE aspects on tourist visits to Malang in the New Normal Era. Researchers conducted this study as an effort to provide answers that aspects of MICE have an effect in increasing tourist visits to Malang during the recovery of the tourism sector in the new normal era. This study research uses quantitative method by describing secondary data through archives and records obtained from the Dinas Kepemudaan, Olahraga dan Pariwisata Kota Malang. The results showed that the simultaneous test (Fhitung =74.6 > F table =3.48), then the variable Meeting (X1), Incentive (X2), Convention (X3), Exhibition (X4) stimultan significantly and positively affect the variable tourist visits (Y). The test result t (partial) on the Meeting variable (X1) has a (thitung 2,720 > T table 2,262) and Convention (X3) has a (thitung 3,457 > T table 2,262) so that the variable Meeting (X1) and Exhibition (X3) have a significant effect on tourist visits. In variable Incentive (X2) has a (thitung 1,479 < T table 2,262) and Variable Exhibition (X4) has a (thitung 0.501 < T table 2,262), so the Incentive variable (X2) and Exhibition (X4) have no significant effect on tourist visits.The result of multiple correlation coefficients (R) is 0.980; shows that together there is a strong and direct relationship between meeting variables (X1), Incentive (X2), Convention (X3), Exhibition (X4) with tourist visits (Y) of 98% while 2% are influenced by other variables outside of this study. The more MICE in Malang, the more tourists visit Malang.